Low-complexity interference variance estimation methods for coded multicarrier systems: application to SFN - Caus, Marius; Perez Neira, Ana I; Renfors, Markku (EURASIP journal on advances in signal processing, 2013)
For single-frequency network (SFN) transmission, the echoes coming from different transmitters are superimposed at the reception, giving rise to a frequency selective channel. Although multicarrier modulations lower the dispersion, the demodulated signal is sensitive to be degraded by inter-symbol interference (ISI) and inter-carrier interference (ICI). In view of this, we use channel coding in conjunction either with filter bank multicarrier (FBMC) modulation or with orthogonal frequency division multiplexing (OFDM). To deal with the loss of orthogonality, we have devised an interference-aware receiver that carries out a soft detection under the assumption that the residual interference plus noise (IN) term is Gaussian-distributed. To keep the complexity low, we propose to estimate the variance of the IN term by resorting to data-aided algorithms. Experimental results show that regardless of the method, FBMC provides a slightly better performance in terms of coded bit error rate than OFDM, while the spectral efficiency is increased when FBMC is considered.